Modern concepts of water legislation in water relations theory (Journal of actual problems of jurisprudence, 2022)
Sound use and protection of water as well as comprehensive legal regulation of water relations, i.e., legislative framework thereof, are core issues in the system of modern water relations and law.  Despite the fact that the concept, the meaning and the contents of modern water legislation (being an independent area of law) in Kazakhstan legal science are analyzed and covered to a great extent, numerous matters calling for immediate answers still arise in real life in the sphere of legal regulation of water relations. Unfortunately, contemporary water legislation is not able to absolutely govern water relations. It requires further development and improvements.Environment protection and rational use of water resources together with legislative framework implying integral regulation of all water relations are considered a top priority strategic direction of the development policy of the Republic of Kazakhstan, a law-governed state respecting the ultimate value of man, his/her life, rights and freedoms. Therefore, the realities of current life place new demands on the quality of water legislation and the legal regulation of water relations via its water law being a separate area of Kazakhstan legal environment.Keywords: Water law, water legislation, water legal relations, sound use of water resources, water relations theory, legal framework.